Viral Etiology of Acute Diarrhoea among Children Attending Selected Hospitals in Nasarawa West, Nigeria - Ismaila Ibrahim; Ismaila Abdulraufu; Ikenna Daniel Uguru; Mitsan Olley; Daniel Ugbomoiko Ohilebo; David Ishaleku; Rahila Ukwo Usman; Nelson Maryoms Gideon; Legbel Ikenna Uguru; Sheidu Mohammed Jamiu (International Journal of Global Health and Epidemiology, 2026)
Background: Acute diarrhoea caused by viral agents is a common cause of illness among children under five years of age, especially in developing countries where poor sanitation, unsafe drinking water, and limited healthcare services remain a major concern. In Nasarawa West, however, limited data are available regarding the viral cause of acute diarrhoea among children under five. Objective: This study evaluated the viral etiology, seasonal distribution, associated risk factors and clinical presentation patterns of acute diarrhoea among children attending hospitals in the Nasarawa West Senatorial District, Nigeria. Methods: A hospital-based cross-sectional study was conducted among 420 children aged 0-60 months presenting with acute diarrhoea between June 2024 and July 2025. Stool samples were collected and assessed for their colour and consistency. The samples were analyzed using a commercially available Certest ROTA+ADENO+NORO one-step combo card test (CertestBiotec S.L, Spain) following the manufacturer’s instructions. Socio-demographic and clinical data were obtained using structured questionnaires. Results were interpreted using SPSS version 29.0 (IBM Corp., USA). Descriptive statistics, the Chi-square test, and Fisher’s exact test were used to summarize and assess associations between categorical variables, with statistical significance set at P< 0.05. Results: Out of 420 diarrhoeic stool samples from children aged 0–60 months, 84 (20.0%) tested positive for viral pathogens; 35 (41.7%) were co-infections. Rotavirus was predominant (76.2%), followed by adenovirus (14.3%) and norovirus (9.5%). Bivariate analysis identified age and gender as significant predictors. Children aged 25-36 months had the highest prevalence (55.6%) and higher odds of infection than those aged 0-12 months (AOR = 5.97, P < 0.001). Males were more infected than females (24.1% vs 13.8%; AOR = 2.00, P = 0.009). Significant environmental and behavioural risks included mixed feeding (82.4%), stream water consumption (25.9%), daycare attendance (P = 0.022), sanitation type (P< 0.001), and a lack of regular handwashing (34.4% vs 10.9%, P< 0.001). Vomiting (χ² = 8.88, OR = 0.40, P = 0.003), dehydration (χ² = 12.89, OR = 2.40, P< 0.001), and rotavirus vaccination status (χ² = 29.44, OR = 0.11, P< 0.001) were significantly associated with virus detection. Whereas no significant associations were observed for fever, diarrhoeal frequency, or stool appearance (P> 0.05). Conclusion: The findings from this study demonstrate the significant role of enteric viruses in childhood gastroenteritis in Nasarawa West, Nigeria, with rotavirus being predominant. The study emphasizes the need for improved vaccination coverage, better sanitation practices and continuous sensitization to reduce the burden of viral diarrheal diseases among children.